Gendered trait preferences for direct-seeded rice in Bihar, India - Connor, M.; Munshi, S. (2024)
Direct-seeded Rice (DSR) has been promoted in several areas in India to improve resource use efficiency, especially water use efficiency. It is also seen as a climate mitigation strategy as it reduces harmful greenhouse gas emissions due to reduced water use. Currently, rice breeding activities center around the creation of germplasm that is suitable to be directly seeded into the soil. There is a need to assess the target product profiles regarding their applicability under direct-seeded conditions. The current study will evaluate men's and women’s trait preferences for DSR. Focus group discussions with farmers were held in Bihar, India one of the largest areas where DSR is introduced and practiced. During the discussion, individual and group preferences were elicited through a trait-card sorting exercise where farmers had to trade off traits in several sorting rounds. Results show that preferences are heterogeneous. Preferences revolve around conditions farmers experience in the field, such as resistance to insects or abiotic stresses like heat and cold tolerance. These are similar for men and women. However, more women selected ‘stays fresh longer after cooking’, which relates to retaining water longer and not drying out too quickly after cooking, than men indicating that this trait is important to women. The poster will further highlight specific combinations of preferences for both men and women.